1990
DOI: 10.1210/edrv-11-1-124
|View full text |Cite
|
Sign up to set email alerts
|

Placental Steroid Hormone Biosynthesis in Primate Pregnancy*

Abstract: Substantial advances in our understanding of placental function have resulted from recent establishment of in vitro approaches, such as cell culture, and application of molecular methods to study placental steroidogenesis. Insight into the processes of placental cell differentiation and hormonal function has been gained from culture of relatively pure preparations of cytotrophoblast. Various factors, e.g. cAMP and peptide growth factors, have been shown to have striking effects on progesterone and estrogen for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
147
1
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(150 citation statements)
references
References 274 publications
(259 reference statements)
1
147
1
1
Order By: Relevance
“…In isolated muscle, increased lactate release and reduced pyruvate oxidation were observed after exposure to 1 μmol/l progesterone, a concentration that is reached in plasma of pregnant women and rats [3,4]. Hence, a surplus of lactate from skeletal muscle could contribute to elevated plasma concentrations as well as to increases in hepatic lactate uptake and in gluconeogenesis from lactate of pregnant rats [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In isolated muscle, increased lactate release and reduced pyruvate oxidation were observed after exposure to 1 μmol/l progesterone, a concentration that is reached in plasma of pregnant women and rats [3,4]. Hence, a surplus of lactate from skeletal muscle could contribute to elevated plasma concentrations as well as to increases in hepatic lactate uptake and in gluconeogenesis from lactate of pregnant rats [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…While several peptide and steroid hormones could make a contribution, a strong line of evidence points at a predominant role of circulating progesterone, which during the course of pregnancy increases in tight association with the reduction in insulin-stimulated glucose disposal [3,4]. The presumptive function of progesterone as a physiological modulator of glucose homeostasis is supported by parallel fluctuations of endogenous plasma progesterone concentrations and insulin sensitivity during the human menstrual cycle [5,6], as well as by a correlation between the plasma concentrations of progesterone and glucose in female mice studied randomly during their cycle [7].…”
mentioning
confidence: 99%
“…Estrogen and progesterone are necessary to establish and sustain pregnancy in mammals (1,31,42). Steroid synthesis in pregnancy involves the maternal ovarian corpus luteum, the placenta, and, in some species, the fetus as well.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that estrogen, the levels of which increase with advancing human and baboon pregnancy [25], stimulated placental trophoblast VEGF expression in the baboon [11,12]. In contrast, estrogen decreased the expression of Ang-1 in the lung, kidney and heart [26].…”
Section: Discussionmentioning
confidence: 98%